2021
DOI: 10.3389/fpls.2021.589940
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Antigens Expressed in Plants Detect Antibody Responses in COVID-19 Patients

Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has swept the world and poses a significant global threat to lives and livelihoods, with 115 million confirmed cases and at least 2.5 million deaths from Coronavirus disease 2019 (COVID-19) in the first year of the pandemic. Developing tools to measure seroprevalence and understand protective immunity to SARS-CoV-2 is a priority. We aimed to develop a serological assay using plant-derived recombinant viral proteins, which rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…We expressed an RBD variant that was previously produced in mammalian or insect cells ( Stadlbauer et al, 2020 ; Klausberger et al, 2021 ) and observed low expression levels and high amounts of homodimers. Recombinant SARS-CoV-2 RBD variants have recently been produced in N. benthamiana using different transient expression systems ( Diego-Martin et al, 2020 ; Mamedov et al, 2020 ; Rattanapisit et al, 2020 ; Makatsa et al, 2021 ). Diego-Martin et al (2020) used a MagnICON-based expression vector to produce a His-tagged RBD variant carrying the same amino acid region (R319-F541) as present in our RBD.…”
Section: Discussionmentioning
confidence: 99%
“…We expressed an RBD variant that was previously produced in mammalian or insect cells ( Stadlbauer et al, 2020 ; Klausberger et al, 2021 ) and observed low expression levels and high amounts of homodimers. Recombinant SARS-CoV-2 RBD variants have recently been produced in N. benthamiana using different transient expression systems ( Diego-Martin et al, 2020 ; Mamedov et al, 2020 ; Rattanapisit et al, 2020 ; Makatsa et al, 2021 ). Diego-Martin et al (2020) used a MagnICON-based expression vector to produce a His-tagged RBD variant carrying the same amino acid region (R319-F541) as present in our RBD.…”
Section: Discussionmentioning
confidence: 99%
“…Plants are a good alternative for the production of eukaryotic proteins, particularly using transient expression systems based on viral vectors (Gleba et al, 2007;Pogue et al, 2010). In fact, some SARS-CoV-2 proteins have already been made in plants (Burnett and Burnett, 2019;Sainsbury, 2020;Makatsa et al, 2021;Siriwattananon et al, 2021), including N (Diego-Martin et al, 2020, although the suitability of plant-made N for detection and diagnosis of antibodies in samples of human sera has not been tested yet. In addition to these technical advantages, plant production of recombinant proteins presents an important economic advantage in terms of production costs, which becomes an important aspect when massive production is required.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, another study has been published showing the usefulness of other plant-produced SARS-CoV-2-derived antigens, the S (or "spike") protein and its Receptor-Binding Domain (RBD) (Makatsa et al, 2021). Apart from the antigens used, the main difference with our study is that Makatsa et al used a lower number of samples in the validation (77 positive, 58 negative), that IgA and IgM were also tested, and that IgA/IgG in saliva were also evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…This ELISA method was adapted from an FDA-approved protocol [ 42 ], with the modification that S1 was cloned, expressed and purified from Nicotiana benthamiana plants. Following coating of 96-well plates (Nunc MaxiSorp, Thermo Fisher, Waltham, Massachusetts, United States) with purified recombinant S1, individual patient samples were diluted 1:50 in PBS and added for 2 h at room temperature; detection was via a goat anti-human IgG (Fc-specific) peroxidase conjugate, as described [ 41 ] Thresholds for true positive signal were determined using the mean plus 2 standard deviations of the data from pre-pandemic controls (n = 58).…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA). ELISA assays were carried out to detect IgG binding to the S1 domain of the spike protein, as previously described [41]. This ELISA method was adapted from an FDA-approved protocol [42], with the modification that S1 was cloned, expressed and purified from Nicotiana benthamiana plants.…”
Section: Confirmatory Testsmentioning
confidence: 99%